Postmortem sa kudeta - Institute for Filipino Cinema; Aguilar, Mila. ([Quezon City] The Institute, 1989)
The December, 1989 coup attempt from the point of view of the victims, businessmen, Makati residents and cause-oriented groups.
VHS
Host, Ma. Ernie Selvido; editor, Mel L. Bacani III
Keywords: Philippines -- History -- Coup d'etat, 1989.; Philippine history; Politics and government